A 9.19 nW hybrid OTA - Source follower biquad lowpass filter - Surachoke Thanapitak (2018)
© 2014 IEEE. The hybrid fully differential second order Gm - C lowpass filter constructed from an operational transconductance amplifier and a PMOS source follower is presented in this paper. This proposed LPF is simulated using 0.35 μm standard CMOS process and consumes 9.19 nW at 1.5 V power supply for 100 Hz bandwidth. The bandwidth of this proposed LPF is tunable from 10 Hz to 1 kHz. The benchmarks between this LPF and the other recent work exhibit an improvement on linearity, dynamic range and FoM.